Synthesis of renewable aviation fuel additives with aromatic aldehydes and methyl isobutyl ketone under solvent-free conditions. Issue 2 (21st December 2020) - Han, Fengan; Xu, Jingyuan; Li, Guangyi; Xu, Jilei; Wang, Aiqin; Cong, Yu; Zhang, Tao; Li, Ning
Abstract : High-density and low freezing point dicycloalkanes were synthesized by the aldol condensation of methyl isobutyl ketone with aromatic aldehydes followed by hydrodeoxygenation under solvent-free conditions. Abstract : Aviation fuel range high-density bicycloalkanes were selectively synthesized with methyl isobutyl ketone (MIBK) and aromatic aldehydes which can be derived from lignocellulose. First, a series of aviation fuel precursors were obtained by the solvent-free aldol condensation of methyl isobutyl ketone (MIBK) and aromatic aldehydes. Among the investigated catalysts, Amberlyst-15 resin exhibited the highest activity. On the basis of characterization, the good performance of Amberlyst-15 resin can be attributed to its bigger surface area, and higher acid site amount and acid strength. Subsequently, the aldol condensation products were further converted to bicycloalkanes by solvent-free hydrodeoxygenation (HDO). A commercial Ru/C catalyst exhibited the highest activity for the HDO process. Over it, high yields (∼95%) of aviation fuel range bicycloalkanes were achieved under mild conditions. According to characterization results, the excellent performance of the Ru/C catalyst might be rationalized by its relatively higher acid strength and better metal dispersion. The bicycloalkanes obtained in this work have high densities (0.895–0.902 g mL −1 ) and low freezing points (223.2–230.0 K). In real applications, they can be used as high-density aviation fuels or additives to improve the volumetric heat values and thermal stability of current aviation fuels.